Μελέτη δραστηριοτήτων για μελλοντικά σενάρια θαλάσσιου χωροταξικού σχεδιασμού στη Κύπρο με τη χρήση ΓΣΠ - Ανδρέου, Χριστιάνα (Τμήμα Πολιτικών Μηχανικών και Μηχανικών Γεωπληροφορικής, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2015)
Marine spatial planning is a new field of study and capabilities, which rational use can provide an integrated planning of marine areas, respecting the environment without degradation of socio-economic objectives. The need to study marine spatial planning in this area occurs from the existence of intense activity due to the presence of industrial and energy infrastructure, as well as the position of the region which favors fishing. For this purpose this thesis studies and records activities, which will be the pillar on which it will be supported to find scenarios for maritime spatial planning, which will be the tool to properly manage the area used in a way that favors the economy, but without effecting the environment. Therefore in this thesis, there has been a general overview on the implementation of Maritime Spatial Planning in the world and how it primarily affects changes in water rules. Subsequently, the main pillars, energy, environment and tourism, were separated in the coastal and marine area of Limassol and then analyzed based on the universal needs they serve. Based on European and Cypriot instructions and laws, and empirical applications and examples of studies in the past, the conflicting uses became identified. The results will appear in the form of maps, with the help of GIS. The data used is restricted, and require high importance for this purpose. In conclusion, this thesis reflects the Cyprus reality as regards maritime and coastal activities and how they collide with each other.
Keywords: Marine spatial planning; Energy; Environment; Tourism; Coastal and marine area of Limassol; GIS; Θαλάσσια χωροταξία; Ενέργεια; Περιβάλλον; Τουρισμός; Παράκτια και θαλάσσια περιοχή της Λεμεσού; Γεωγραφικά συστήματα πληροφοριών